Mycoplasma bovis-pneumonia and polyarthritis in feedlot calves in Argentina: First local isolation - Canton, German Jose; Llada, Ignacio Mariano; Margineda, Carlos Augusto; Urtizbiria, Facundo Nahuel; Fanti, Sofía; Scioli, Maria Valeria; Fiorentino, María Andrea; Louge Uriarte, Enrique Leopoldo; Morrell, Eleonora Lidia; Sticotti, Erika; Tamiozzo, Pablo (Asociación Argentina de Microbiología, 2022)
Bovine respiratory disease (BRD) is one of the most frequent clinical concerns in weaned calves after their arrival at the feedlot. This work reports the first local isolation of Mycoplasma bovis from feedlot calves with pneumonia and polyarthritis in Argentina. Twenty four out of 545 calves showed progressive, subacute to chronic respiratory distress, coughing, and fever. Thirty percent of the affected calves also showed lameness and swelling of elbow or carpal, and knee or tarsal joints. Five necropsies were performed and severe multifocal to coalescent pulmonary nodules, containing white-yellowish caseous exudate encircled by fibrous tissue, and fibrinonecrotic arthritis and tenosynovitis were detected. Mycoplasma was isolated from lung and joint samples. The 16S-23S rRNA ITS consensus sequence obtained from these isolates showed 100% similarity with the same region of M. bovis strains. Since there are no commercially available vaccines in the region for the prevention and control of M. bovis pneumonia and arthritis, surveillance is a priority to reduce the source of disease to naïve animals.